Two-port laparoscopic appendectomy is more benefecial than open appendectomy in early acute appendicitis - Budipramana, Vicky S (Folia Medica Indonesiana, 2017)
Open appendectomy has already commonly been performed to treat acute appendicitis, but the relatively more painful and longer incision scar becomes a cosmetical problem. Two port laparoscopic appendectomy can be performed safely, less painful and leaving only two small incision scars. The aim of the study was to evaluate the benefit of two-port laparoscopic appendectomy and that of with open appendectomy in the case of early acute appendicitis. An observational study was conducted from 2012 to 2014; to compare the operating time, post operative pain and wound infection in early acute appendicitis, performed with two-port laparoscopic appendectomy and with open appendectomy. The statistical analysis in this study uses t-test. There were 114 patients (73 men and 41 women) divided into two groups based on the choice made by the patients themselves. The number of samples performed with two-port laparoscopic appendectomy was 64 and that with open appendectomy was 46. Four patients were excluded from this study. In analysis using t-test, we found that the two-port laparoscopic appendectomy was more beneficial than open appendectomy. There was a significant difference between the two groups, the length of operation time was 37.22 minute in two-port laparoscopic appendectomy and 43.83 minute in open appendectomy (p=0.00), VAS pain score was 1.58 in two-port laparoscopic appendectomy and 2.30 in open appendectomy (p=0.00) and no post operative wound infection in both two groups. The conclusion is two-port laparoscopic appendectomy technique is faster and less painful and the same risk of wound infection than open appendectomy in early acute appendicitis.